2019
DOI: 10.1111/jce.13936
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon ablation for persistent atrial fibrillation in patients without left atrial fibrosis

Abstract: Introduction: The role of cryoballoon (CB) pulmonary vein isolation (PVI) for patients with persistent atrial fibrillation (AF) is controversial, since long-term success can be poor. We performed left atrial voltage mapping before CB PVI and determined AF-free survival depending on the extent of low-voltage areas (LVAs). Methods and Results:We consecutively enrolled 60 patients with persistent AF (average age, 60.6 ± 12.9 years; CHA 2 DS 2 VASc score, 2.3 ± 1.6; and left atrial size 46.0 ± 5.2 mm) who were pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…1). Of a total of 325 citations identified for full-text review, 4 were eligible for inclusion in the present analysis [4,[18][19][20]. Reasons for exclusion included study design (e.g., retrospective studies), population (e.g., paroxysmal AF, long-standing PsAF), irrelevant intervention or comparator, or if the study did not report the outcomes of interest.…”
Section: Literature Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Of a total of 325 citations identified for full-text review, 4 were eligible for inclusion in the present analysis [4,[18][19][20]. Reasons for exclusion included study design (e.g., retrospective studies), population (e.g., paroxysmal AF, long-standing PsAF), irrelevant intervention or comparator, or if the study did not report the outcomes of interest.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…A total of 389 patients with PsAF were pooled from four CB trials [4,[18][19][20]. The mean (SD) age of the pooled CB cohort was 63.1 (10.2) years.…”
Section: Study Characteristics and Prognostic Factors And Treatment-effect Modifiersmentioning
confidence: 99%
“…The importance of LA dimensions in the settings of CB‐A has been recently confirmed by Akkaya et al, as they showed that left atrial area >21 cm 2 was a significant predictor of recurrence in a population of 101 patients undergoing CB‐A with second‐generation CB. Furthermore, in a recent work from Gramlich et al, the degree of atrial fibrosis was proved to correlate with the risk of AF recurrence at 1 year follow‐up after CB‐A in 60 patients with persistent AF, therefore stressing the relevance of possible residual substrate areas besides PVs in those patients with a large extent of low‐voltage areas and more generally of the LA disease.…”
Section: Discussionmentioning
confidence: 96%
“…dergoing CB-A with second-generation CB. Furthermore, in a recent work from Gramlich et al,34 the degree of atrial fibrosis was proved to correlate with the risk of AF recurrence at 1 year follow-up after CB-A in 60 patients with persistent AF, therefore stressing the relevance of possible residual substrate areas besides PVs in those patients with a large extent of low-voltage areas and more generally of the LA disease.Interestingly, most of episodes of restoration of SR (69.8%) in our case group occurred while performing right PVs cryo-applications.Despite the frequent localization of focal AF triggers in the RSPV35 and the central role of the cryo-applications on the right-side PVs in modifying the cardiac autonomic nervous system,36,37 the electrophysiological and clinical significance of this observation remains unclear; moreover, since right PVs cryo-applications are the ones performed in the second half of the procedure, some role and/or a cumulative effect of previous cryo-applications on the results described cannot be excluded. Since the area targeted by CB is wide and antral,38 the extent of the lesion created by the cryo-application may also involve other structures of the LA which may have a role in maintaining AF.…”
mentioning
confidence: 94%
“…LA fibrosis, a hallmark of atrial remodeling, has been discriminated as a relevant predictor of AF recurrence after successful catheter ablation 25 . In this context, the recent study by Gramlich et al 26 demonstrated that the presence of LA low‐voltage areas significantly affected the success of CB‐guided PVI.…”
Section: Discussionmentioning
confidence: 99%